Cysticercal encephalitis with cortical blindness. (21st October 2010) - Prasad, Rajniti; Thakur, Neha; Mohanty, C; Singh, M K; Mishra, O P; Singh, Utpal Kant
Abstract : The authors report a 6-year-old boy, who had presented with low-grade fever, altered sensorium, headache and seizure for 5 days. On examination, he had features of raised intracranial pressure with left VI cranial-nerve palsy and bilateral extensor plantar response. CT scan showed multiple calcifications in cerebral cortex. MRI cranium showed multiple cysts involving whole of the brain. He was diagnosed as having cysticercal encephalitis, based on immunological and imaging study. He was managed with 20% mannitol, phenytoin and albendazole, and regained consciousness 7 days later, but had residual neurological deficit as left-lower-limb monoparesis and visual acuity of just projection of rays (PR+) and perception of light (PL+).